1986
DOI: 10.1149/1.2108574
|View full text |Cite
|
Sign up to set email alerts
|

A Platinized Titanium Anode for Chromium Electroplating

Abstract: There are two types of electrolyte for chromium electroplating: the Sergent bath and the chromate solution containing fluorine compound. The Sergent bath is an acidified chromate solution consisting of some 250 g/liter CrO~, and easy to operate. However, the current efficiency for chromium deposition is low, about 10% or less. Metal deposition no longer takes place if the electric circuit is once interrupted. This is probably due to rapid passivation of the metal surface, and it is troublesome. Therefore, the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

1986
1986
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 2 publications
0
3
0
Order By: Relevance
“…This gives good results but is not always practical. Platinized titanium anodes with thermally deposited indium dioxide are proposed [125]. Titanium anodes coated with PtO 2 are recently recommended for chromium plating [126].…”
Section: Anodesmentioning
confidence: 99%
“…This gives good results but is not always practical. Platinized titanium anodes with thermally deposited indium dioxide are proposed [125]. Titanium anodes coated with PtO 2 are recently recommended for chromium plating [126].…”
Section: Anodesmentioning
confidence: 99%
“…19 .20 McIntyre2 1 reported that iridium oxide coatings tested for use as anodes during cathodic electrodeposition of organic coatings showed no degradation and an estimated service life of four years, while in similar tests, ruthenium oxide coatings were marginal and cobalt oxide coatings were unsatisfactory. Hine et al 22 tested a platinized titanium sheet loaded with thermally deposited iridium oxide for use in chromium electroplating. Hardee et al 23 have reviewed the use of DSAtype anodes for high-speed electroplating and electrogalvanizing.…”
Section: Electroplating and Electrogalvanizingmentioning
confidence: 99%
“…In addition, corrosion mechanism of the lead-alloy has been intensively investigated in sulphuric acid solutions. [13][14][15] For anode in solution containing chromium, some researches indicate that the alloying additions in lead base alloys anode affect the microstructure and electrochemical characteristics of active materials, 16 corrosion rate 17 and layers structure 18 on the electrode. However, few reports regarding anode surface action in the more aggressive (strong oxidation and high acidity) environment of CrO 3 solution at high current densities of above 10 A/dm 2 are available in literature.…”
mentioning
confidence: 99%